Tratamiento de la información periodística en redes sociales y su impacto comunicacional en los habitantes de la Parroquia San Camilo Sector Promejoras año 2021 - Alvarado Sucre, Angel José (2021)
This project aims to demonstrate that the communicational impact on the inhabitants of a sector also depends on the treatment of journalistic information on social networks, not negative but positive within a community, whether it is virtual or physical, being that the information received by a sector It can be misrepresented, depending on the issuer at the time of posting in order to inform a community. There are negative precedents for the inadequate treatment of the information that is given in social networks, where due to the inadequate use of that information, children, adolescents, adults are involved, creating a negative psychological space in the family environment, aspects of the information must be analyzed in the social environment, this research highlights important points that show that secrecy and professionalism must be maintained in the treatment of information, which for many can be suggestive and cause of attraction in news events that have occurred in the Quevedo canton, and this information has reached the Promejoras Sector, which for those who live there have been involved either directly or indirectly, causing psychological trauma, in these families morbid, fear, discrimination, marginalization, issues of human rights violations, They are created by the impact of the bad treatment of journalistic information on social networks in the communicational field.